Factors Related to 30 day Mortality in Critically Ill Patients withInvasive Candidiasis in Cipto Mangunkusumo Hospital - Ardian, Ardi; Pitoyo, Ceva W; Adhitianingsih, Dita; Santoso, Widayat Djoko; Setiati, Siti (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Mortality rate of invasive candidiasis is still high, approximately 30-70%. Every study has a variety mortality rate depend on study design and sample. There is no data in Indonesia about profile and mortality factors analysis in critically ill patients with invasive candidiasis. Methods. The Study design was cross sectional. We studied 102 hospitalized critically ill patients with invasive candidiasis. The demographic, clinical and laboratory data, the risk factors for invasive candidiasis and the outcome of each patient in 30 days were recorded. An analysis bivariate with chi square or Fisher’s test was carried out to analyse some factors such as age > 60 years old, severe sepsis, APACHE score > 20, respiratory failure, renal failure, delayed antifungal treatment > 72 hours after positive culture, Charlson index score, and ICU or non ICU patients. The logistic regression of multivariate analysis was carried out to identify the most influence of all mortality factors. Results. Among 102 identified sample, the majority was male (52.9%), the median age was 53 years old and the mortality rate was 68,6%. Laboratory candida findings came from blood sample (candidemia) (98.03%), liquor cerebrospinal (1.5%) and retina exudate (1.5%). The most common candida species were candida non albicans especially Candida tropicalis (34.3%) and Candida parapsilosis (34.3%). The risk factors for invasive candidiasis from this study related to underlying disease were sepsis (78.9%), malignancy (42.15%), diabetes mellitus (29.4%) and related to therapy or treatment were the usage of broad spectrum antibiotic (99%), central vein catheter (77.5%), and parenteral nutrition (70.6%). The result from multivariate analysis, severe sepsis (p 0.001, OR 7.7, IK95% 2.4 – 24.7), Charlson Index ≥3 (p 0.022, OR 3.5, IK95% 1.2–10.2), and respiratory failure (p 0.066, OR 2.7 IK95% 0.9 – 8.0) were independently associated with mortality. Conclusions. In Cipto Mangunkusumo hospital, most critically ill patients with invasive candidiasis was male, median age was 53 years old, and mortality rate was 68,6%. The most species candida caused infection were Candida tropicalis and Candida parapsilosis. The most risk factors of invasive candidiasis from underlying disease was sepsis and from the treatment was the usage of broad spectrum antibiotic. Severe sepsis, and Charlson index ≥3 were associated with a 30 day mortality in critically ill patients with invasive candidiasis.